Cross-sectional study of urethral exposures at last sexual episode associated with non-gonococcal urethritis among STD clinic patients. (4th September 2018) - Chambers, Laura C; Morgan, Jennifer L; Lowens, M Sylvan; Robinson, Tashina S; Romano, Sarah S; Leipertz, Gina L; Hughes, James P; Golden, Matthew R; Khosropour, Christine M; Fredricks, David N; Manhart, Lisa E
Abstract : Objective: Although Chlamydia trachomatis (CT) and Mycoplasma genitalium (MG) are major causes of non-gonococcal urethritis (NGU), up to 50% of cases are of unknown aetiology. We sought to identify urethral exposures at last sexual episode associated with NGU and non-CT/non-MG NGU to identify anatomical sites from which aetiologically relevant micro-organisms may be acquired. Methods: We enrolled STD clinic patients with and without NGU assigned male sex at birth and age ≥16 into a cross-sectional study. NGU was urethral symptoms or visible discharge plus ≥5 polymorphonuclear leucocytes without Neisseria gonorrhoeae . Urine was tested for CT and MG (Aptima). We used logistic regression to estimate the association between urethral exposures at last sex and NGU separately among cisgender men and transgender women who have sex with men (MSM/TGWSM) and cisgender men who have sex with women (MSW). Results: Between 8 August 2014 and 1 November 2017, we enrolled 432 patients, including 183 MSM/TGWSM (118 NGU+, 65 NGU−) and 249 MSW (126 NGU+, 123 NGU−). The mean age was 34; 59% were white. CT and MG were detected in 72 (30%) and 49 (20%) NGU+ participants, respectively. Compared with MSM/TGWSM reporting only non-urethral exposures at last sex, those reporting insertive anal intercourse (IAI) only (adjusted OR (AOR)=4.46, 95% CI 1.09 to 18.19) and IAI with insertive oral sex (IOS) (AOR=7.88, 95% CI 2.67 to 23.26) had higher odds of NGU. MSM/TGWSM reporting IOS only had no significant increased odds (AOR=1.67, 95% CI 0.58 to 4.85). Compared with MSW whose only urethral exposure at last sex was vaginal sex (VS), MSW reporting IOS and VS had similar odds of NGU (OR=0.84, 95% CI 0.50 to 1.41). The results were similar for non-CT/non-MG NGU. Conclusions: Among MSM/TGWSM, IAI may lead to transmission of yet-unidentified rectal micro-organisms that cause non-CT/non-MG NGU, in addition to transmission of known pathogens. Sites of urethral exposure appear less important for understanding NGU risk among MSW due to minimal variation in behaviour.